2019
DOI: 10.1002/da.22889
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk factors among youth at high risk for suicide in South Africa and Guyana

Abstract: Introduction: Suicide is the second leading cause of death among youth worldwide, but low-and middle-income countries (LMICs) account for 78% of all suicides. The LMICs South Africa and Guyana rank high in the global suicide rates. To better understand and prevent suicide among the youth, the present study targets youths at high risk for suicide, in an LMIC, to contextually and representatively identify clinical risk factors for suicide.Methods: One hundred-ninety youths, aged 11-21, separated from biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 49 publications
1
6
0
1
Order By: Relevance
“…This study also found a statistically significant difference in the characteristics of suicide according to gender. Studies in other countries have indicated that girls report more emotional symptoms (e.g., depression) and interpersonal conflict, while boys are more often associated with engagement in violent experiences and anger-related symptoms [ 2 , 33 , 34 ] The current study’s findings are similar to those of earlier studies [ 35 ] and confirm that the effects of risk factors differ by gender. Boys tend to show more externalized problems (anger, difficulties with impulse control, risk-taking, and physical aggression) than girls, whereas girls tend to show more internalized problems (depressive symptoms and social exclusion) than boys [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…This study also found a statistically significant difference in the characteristics of suicide according to gender. Studies in other countries have indicated that girls report more emotional symptoms (e.g., depression) and interpersonal conflict, while boys are more often associated with engagement in violent experiences and anger-related symptoms [ 2 , 33 , 34 ] The current study’s findings are similar to those of earlier studies [ 35 ] and confirm that the effects of risk factors differ by gender. Boys tend to show more externalized problems (anger, difficulties with impulse control, risk-taking, and physical aggression) than girls, whereas girls tend to show more internalized problems (depressive symptoms and social exclusion) than boys [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…There is growing evidence highlighting the magnitude and rising prevalence of mental disorders, mental health symptoms and substance use among youth in Africa [ 2 , 8 , 9 , 28 ]. More recently suicide is becoming another growing topic of concern [ 29 , 30 ]. COVID-19 has amplified these existing problems for young people on a national, regional, and global scale [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-five (74•3%) of the studies reported prevalence estimates, though none reported lifetime, 12-month, 6month, and 1-month estimates, with 12-month estimates favoured by the majority (n = 30; 54•5%). As shown in Table 2, the reported lifetime prevalence estimates ranged from 1•4% to 48•3% [28,50]; the 12-month prevalence estimates varied between 0•9% and 35•8% [52,72]; the reported 6-month prevalence ranged from 7•4% to 22•7% [55,79]; and the 1-month reported prevalence estimates varied between 1•9% and 26•4% [31,58].…”
Section: Main Findingsmentioning
confidence: 99%